2009
DOI: 10.1215/15228517-2008-092
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric glioblastomas: A histopathological and molecular genetic study

Abstract: Glioblastoma multiforme (GBM) occurs rarely in children. Relatively few studies have been performed on molecular properties of pediatric GBMs. Our objective in this study was to evaluate the genetic alterations in pediatric GBM (age < or = 18 years) with special reference to p53, p16, and p27 protein expression, alterations of the epidermal growth factor receptor (EGFR), and deletion of the phosphate and tensin homolog gene (PTEN). Thirty cases of childhood GBMs reported between January 2002 and June 2007 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 33 publications
6
61
1
6
Order By: Relevance
“…İnfant GBM, de novo gelişim gösteren ve tamamen farklı bir antitedir. [5,6] Pediatrik YDG oluşumu, erişkin sekonder GBM patogeneziyle benzerlik gösterir ve p53 mutasyonunun normalden fazla ekspresyonu (%65), PDGF-A ve PDGFR-α (%60) ekspresyonunun artışına neden olarak patogenezde başlatıcı role sahiptir. Ancak pediatrik YDG oluşumu, henüz eriş-kin patogenezi kadar netlik kazanmamıştır.…”
Section: Etyolojiunclassified
“…İnfant GBM, de novo gelişim gösteren ve tamamen farklı bir antitedir. [5,6] Pediatrik YDG oluşumu, erişkin sekonder GBM patogeneziyle benzerlik gösterir ve p53 mutasyonunun normalden fazla ekspresyonu (%65), PDGF-A ve PDGFR-α (%60) ekspresyonunun artışına neden olarak patogenezde başlatıcı role sahiptir. Ancak pediatrik YDG oluşumu, henüz eriş-kin patogenezi kadar netlik kazanmamıştır.…”
Section: Etyolojiunclassified
“…The overexpression of the EGFR protein is observed in 23-40% of patients, and p53 gene mutations are very frequent, occurring in approximately 33-63% of patients (22)(23)(24). The genes overexpressed in GBM usually produce extracellular proteins, thereby providing possible therapeutic targets.…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…The extent of surgical resection coupled with postoperative radiotherapy and chemotherapy seem to prolong survival. Our neuropathology colleagues performed molecular analysis of a subgroup of these patients and concluded that in pediatric primary GBMs, deletion of PTEN, and EGFR amplification were rare, while p53 alterations were more frequent as compared with primary adult GBMs [2].…”
mentioning
confidence: 99%